Incidence and Predictors of Acute Psychological Distress and Dissociation after Motor Vehicle Collision: a Cross-Sectional Study - Lewis, Gemma C. (2014)
OBJECTIVE: The authors examined the incidence and predictors of peritraumatic distress and dissociation after one of the most common forms of civilian trauma exposure: motor vehicle collision (MVC). METHODS: In this study, patients presenting to the emergency department after MVC who were without serious injury and discharged to home after evaluation (n = 935) completed an emergency department interview evaluating sociodemographic, collision-related, and psychological characteristics. RESULTS: The incidence and predictors of distress (Peritraumatic Distress Inventory score ≥ 23) and dissociation (Michigan Critical Events Perception Scale score >3) were assessed. Distress was present in 355 of 935 patients (38%) and dissociation was present in 260 of 942 patients (28%). These outcomes showed only moderate correlation (r = 0.45), and had both shared and distinct predictors. Female gender, anxiety symptoms prior to MVC, and vehicle damage severity predicted both distress and dissociation. Higher socioeconomic status (higher education, higher income, full time employment) had a protective effect against distress but not dissociative symptoms. Better physical health and worse overall mental health were associated with increased risk of dissociation, but not distress. Distress but not dissociation was associated with lower patient confidence in recovery and a longer expected duration of recovery. CONCLUSION: There are unique predictors of peritraumatic distress and dissociation. Further work is needed to better understand the neurobiology of peritraumatic distress and dissociation, and the influence of these peritraumatic outcomes on persistent psychological sequelae.